Assessment of Plant Biodiversity around the Tobolsk Industrial Site. Issue 2 (December 2021) - Kharitontcev, B; Popova, E
Abstract: The article presents the results of comprehensive studies of the plant biodiversity near the industrial zone of the city of Tobolsk, Tyumen Oblast, Russia. Nine species of formation communities were identified: Abies sibirica Ledeb, Pineta (sylvestris), Betuleta (pendula), Betuleta (pubescens), Tilieta (cordata), Populeta (tremula), Saliceta, Prata, Emersiherbosa. Also, eleven associations were identified for the studied communities: fir forest with sedges, linden and birch; mixed small-leaved dark coniferous forest with sedges; low-shrub sphagnum pine forest; steppe birch forest; swampy low-shrub sphagnum birch forest; swampy reedgrass birch forest; linden-birch forest; cereal-horsetail-fern aspen forest; aspen forest with grass layer; aspen forest mixed with birch and sedges; mixed birch-aspen forb forest; maturing aspen-birch forest with hygrophilous grasses.